Variability of noninvasive MRI and biological markers in compensated cirrhosis: insights for assessing disease progression - Christopher R. Bradley; Eleanor F. Cox; Naaventhan Palaniyappan; Guruprasad P. Aithal; Susan T. Francis; Indra Neil Guha (European Radiology Experimental, 2022)
Abstract Background We annually monitored stable compensated cirrhosis (CC) patients to evaluate serial variation in blood serum, liver stiffness, and multiparametric magnetic resonance imaging (mpMRI) measures to provide reference change values (RCV) and sample size measures for future studies. Methods Patients were recruited from a prospectively followed CC cohort, with assessments at baseline and annually over three years. We report on blood markers, transient elastography liver stiffness measures (LSM) and noninvasive mpMRI (volume, T1 mapping, blood flow, perfusion) of the liver, spleen, kidneys, and heart in a stable CC group and a healthy volunteer (HV) group. Coefficient of variation over time (CoVT) and RCV are reported, along with hazard ratio to assess disease progression. Sample size estimates to power future trials of cirrhosis regression on mpMRI are presented. Results Of 60 CC patients enrolled, 28 with stable CC were followed longitudinally and compared to 10 HVs. CoVT in mpMRI measures was comparable between CC and HV groups. CoVT of Enhanced Liver Fibrosis score was low (< 5%) compared to Fibrosis-4 index (17.9%) and Aspartate Aminotransferase-to-Platelet-Ratio Index (19.4%). A large CoVT (20.7%) and RCV (48.3%) were observed for LSM. CoVT and RCV were low for liver, spleen, and renal T1 values (CoVT < 5%, RCV < 8%) and volume (CoVT < 10%, RCV < 16%); haemodynamic measures were high (CoVT 12–25%, RCV 16–47%). Conclusions Evidence of low CoVT and RCV in multiorgan T1 values. RCV and sample size estimates are provided for future longitudinal multiorgan monitoring in CC patients. Trial registration ClinicalTrials.gov identifier: NCT02037867 , Registered: 05/01/2013.